Parents' Anxiety During Children’s Hospitalization - Mbaloto, Freny Ravika; Purwaningsih, Diah Fitri; Mamuaya, Greistinsi Filiandini; Mua, Estelle Lilian; Sekeon, Robi Adikari; Susanto, Denny Fitri (Adi Husada Nursing Journal, 2024)
Illness and hospitalization of a child are very difficult and most often unpredictable situations in the family life cycle. The stress level of the parents of the child who is hospitalized dependson many factors, such as the psychological characteristics of children and parents, children health conditions, and support from family and medical personnel. The purpose of this study was to identify parents' anxiety in dealing with their child's hospitalization. The research design used is descriptive research with a qualitative approach. The population of this study were all parents of children aged 3-6 years who were hospitalized. The sample in this study were 43 parents of children. Sampling was carried out non-probability with a purposive sampling approach with inclusion criteria: parents were biological fathers and mothers of children who were hospitalized, preschool age 3- 6 years old who has a diagnosis of Hyperthermia, DHF, Diarrhea and Vomiting, ARI, Asthma, Traffic Accidents, parents who are willing to sign an informed consent. he results show that the anxiety of parents facing hospitalization is that the dominant child has mild anxiety (62.8%). This study hopes that parents can be involved during treatment.